CONNECTION BETWEEN COMORBID PRIMARY HEADACHE, DEPRESSION AND ANXIETY IN PATIENTS WITH MULTIPLE SCLEROSIS - Andriievska, M. I. (Здобутки клінічної і експериментальної медицини, 2023)
Multiple sclerosis (MS) is a chronic autoimmune disorder of central nervous system that affects young people and progresses to physical disability. Among patient with MS risk of excessive anxiety and depression is quite common. One of the frequent comorbidities of MS is primary comorbid headache. Depression and anxiety might be more prominent on patients with pain comorbidity of MS. The aim – to show the prevalence and frequency of depression and anxiety in a population of patients with MS, with special attention to the group of patients with primary comorbid headache. Material and Methods. MS was confirmed according to the McDonald criteria 2017. Questionnaires Beck Depression Inventory (BDI) for assessment of depression and The Spielberger State-Trait Anxiety Inventory in Hanin`s interpretation (STAI), version for evaluation of reactive anxiety were used. Results. 130 patients with MS were examined with disease duration 8.63±7.49 years. 36.2 % of males (n=47) and 63.8 % of females (n=83) were included. Average score of patients with MS was 40.22±8.89 points that indicates moderate reactive anxiety. BDI score accounted for 14.15±7.58 points that interpretates as mild-to-moderate depression. Patients with MS and comorbid primary headache received the average points of the STAI in Hanin's interpretation – 42.41±7.49 (moderate anxiety); patients with MS without comorbid primary headache – 37.42±9.31 (low or moderate anxiety), but generally this difference did not show statistical significance (p=0.39). Among MS course scores of anxiety was similar between groups, depression score was the highest in group with primary progressive MS (PPMS). Conclusion. The average score of anxiety and depression showed moderate severity among patients with MS. There were not found significance between patients with primary headache comorbidity and without it, although scores between course disease subgroups showed higher points in patients with comorbid primary headache.